2018
DOI: 10.1111/irv.12613
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed tetraplex real‐time RT‐PCR for simultaneous screening of influenza virus types A, B, C and D

Abstract: BackgroundHuman‐ or avian‐to‐swine transmissions have founded several autonomously circulating influenza A virus (IAV) lineages in swine populations that cause economically important respiratory disease. Little is known on other human influenza virus types, like B (IBV) and C (ICV) in European swine, and of the recently detected novel animal influenza virus type D (IDV).ObjectivesDevelopment of a cost‐effective diagnostic tool for large‐scale surveillance programmes targeting all four influenza virus types.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
1
26
0
4
Order By: Relevance
“…Thus, the very low seroprevalence of IDV in domestic pigs in France (this study) and the short shedding period reported after experimental infection [1] probably contributed to the absence of detection of IDV genome in nasal swab samples in this country. Nevertheless, our virological results are consistent with those obtained in a large-scale study conducted on 3753 nasal swabs taken from pigs with respiratory illness, in 682 farms located in twelve European countries, including France but excluding Italy and Luxembourg [22]. Among them, 1166 nasal swabs were sampled in 2015-2017 on pigs reared in France, and they all tested negative towards IDV in a tetraplex RT-qPCR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the very low seroprevalence of IDV in domestic pigs in France (this study) and the short shedding period reported after experimental infection [1] probably contributed to the absence of detection of IDV genome in nasal swab samples in this country. Nevertheless, our virological results are consistent with those obtained in a large-scale study conducted on 3753 nasal swabs taken from pigs with respiratory illness, in 682 farms located in twelve European countries, including France but excluding Italy and Luxembourg [22]. Among them, 1166 nasal swabs were sampled in 2015-2017 on pigs reared in France, and they all tested negative towards IDV in a tetraplex RT-qPCR.…”
Section: Discussionsupporting
confidence: 88%
“…Questions about IDV host range relate especially to the role pigs may play in IDV ecology. Indeed, the virus was first isolated from a pig exhibiting a respiratory syndrome [1]; pigs were demonstrated to be sensitive to IDV infection experimentally [1,21], and similarly to cattle, IDV was isolated or molecularly detected in pigs in different continents, i.e., America [1], Asia [11] and Europe [6][7][8]22]. Serological investigations also confirmed IDV infections in domestic pig and feral swine populations, although with very different positivity rates from one country and/or one study to another [1,7,8,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Since the global dissemination of pH1N1 virus, this lineage has also undergone reassortment with swine IAV strains endemic to the corresponding geographic region (5). Within Europe, this diversification of pH1N1 virus in pigs has increased the circulating swine IAVs from 4 to >25 genotypes (6,7). Diversification has been rapid; pH1N1 reassortant viruses incorporating enzootic swine virus HA and NA, or NA alone, detected during 2010 in the United Kingdom (8) and Italy (9), have emerged.…”
mentioning
confidence: 99%
“…The influenza viruses are classified into types A, B, C, and D on the basis of their core proteins [5]. Among the four influenza types, influenza A viruses cause most of the global flu epidemics, influenza B viruses cause smaller localized outbreaks, influenza C viruses generally cause mild illness, and influenza D viruses are not known to cause illness in people [6][7][8]. Thus, influenza A and B viruses comprise the major respiratory pathogens in humans that cause seasonal flu epidemics [9,10].…”
Section: Introductionmentioning
confidence: 99%